The predictions of the results in a race walking with the use of predictive models - Sudol, G.; Mleczko, E. (Slovak Journal of Sport Science, 2017)
Aim. The issue of forecasting records in measurable sports disciplines has a very long tradition. For this purpose, methods known in mathematical statistics and econometrics are used. To date, approximation theory has not been used to predict the future course of the sports careers among athletes reaching phases of relative stabilization in their results. In this study, we presented our own proposal for adapting predictive models in solving the signalled problem. Basic procedures. Time series of the best results obtained during the 21-year sporting career of the three-time Olympic participant were analyzed. Using the method of least squares for approximation of the results obtained up until the end of the observation, based on the developed curve (parabola) and the nonlinear 2nd grade model (y = ax2+bx+c), we estimated further prospects for the development of sports championship in race-walking for 20 and 50 km distances. Research results. Characteristics of the sports biography provided valuable results to understand the development trends of the contemporary model of a champion in professional sports and to develop training and recruitment concepts for future sports champions. Conclusions. Predictive models should be used both for forecasting the development of sports disciplines and planning the development of careers of players reaching a phase of relative stability in sports performance.